Navigating the landscape of neoadjuvant immunotherapy for NSCLC: progress and controversies - Yuzhu Chen; Fei Qi; Chenhao Sun; Peng Jiang; Xiangyu Xue; Xiaomei Yang; Xiaomi Li; Xin He; Yishuo Wang; Tongmei Zhang (Therapeutic Advances in Medical Oncology)
Recently, attention has increasingly centered on non-small-cell lung cancer (NSCLC) with immune checkpoint inhibitors application. Numerous clinical studies have underscored the potential of immunotherapy in treating resectable NSCLC, highlighting its role in improving patient outcomes. However, despite these promising results, there is ongoing debate regarding the efficacy of immunological combination therapy strategies, the prevalence of treatment-related side effects, the identification of predictive biomarkers, and various other challenges within the neoadjuvant context. Careful consideration is essential to maximize the benefits of immunotherapy for patients with resectable NSCLC. This article offers a detailed overview of recent advancements in neoadjuvant immunotherapy for resectable NSCLC. By examining these developments, we aim to provide new perspectives and valuable insights into the benefits and challenges of applying neoadjuvant immunotherapy in clinical settings.